A method for testing the resistivity of conductive silicon carbide wafers after cutting

By performing limited solution cleaning and specific point distribution resistivity testing after cutting of conductive type silicon carbide wafers, the problem of failure to test resistivity in time in the prior art is solved, and higher testing accuracy and cost savings are achieved.

CN116660628BActive Publication Date: 2025-03-04SICC CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310919290.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-03-04
Estimated Expiration
2043-07-26

AI Technical Summary

Technical Problem

In the prior art, conductive silicon carbide wafers fail to perform resistivity tests in time after cutting, resulting in some unqualified wafers being uploaded to subsequent processing steps, wasting resources and increasing production costs.

Method used

By cleaning a limited type of solution, the cut silicon carbide wafer is cleaned in segments to reduce surface roughness, and resistivity testing is performed using a specific point distribution, and the resistivity testing process is advanced before grinding.

Benefits of technology

It realizes that the resistivity of conductive silicon carbide wafers can be accurately tested after cutting, which improves test accuracy, saves processing costs, and reduces unnecessary wafer damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116660628B_ABST
    Figure CN116660628B_ABST
Patent Text Reader

Abstract

The present application discloses a method for testing the resistivity of a conductive silicon carbide wafer after cutting, which belongs to the technical field of silicon carbide wafers, and includes the following steps: a. Segmented cleaning: placing the cut silicon carbide wafer in a basket, and sequentially soaking it in an acid-base tank containing an organic solvent, an acid or alkali solution, and water, and ultrasonicating it in an organic solvent after cleaning, and drying it; b. Using an FRT surface tester, testing the thickness of multiple points on the surface of the wafer, and finally obtaining the average value of the thickness data; c. Using a non-contact resistivity tester, inputting the average thickness of the wafer, setting the test points according to the point distribution, and testing the probe twice at each point during the test, and finally drawing a resistivity distribution map of the entire wafer surface, and statistically calculating the maximum value, minimum value, and average value. The present application uses a limited type of solution for cleaning, advances the resistivity test to before grinding, and saves costs; matching a specific point distribution provides an accurate basis for judging the quality of the wafer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a method for testing the resistivity of a conductive silicon carbide wafer after cutting, and belongs to the technical field of silicon carbide wafers. Background Art

[0002] The resistivity of conductive silicon carbide wafers is an important parameter, both for characterizing the physical properties of the wafer itself and semiconductor devices. For wafers, resistivity characterizes the growth and doping uniformity of the wafer; for downstream devices, it directly affects other related parameters such as the device's series resistance, capacitance, threshold voltage, and hot carrier degradation of MOS devices. Therefore, the resistivity data of conductive silicon carbide wafers is one of the key parameters that must be tested.

[0003] There are many methods to test the resistivity of conductive silicon carbide wafers, such as the four-probe method, the Van der Pauw method, and the eddy current method. In industry, people generally prefer the eddy current method because it is a non-destructive test. The testing principle of the eddy current method is: an alternating current of a certain frequency flows through a conductive coil to form an alternating magnetic field, and at the same time induces eddy currents on the wafer. The magnetic field changes generated by the eddy currents can be detected by the sensor, so the square resistance of the substrate can be calculated. At the same time, according to the wafer thickness obtained by the test, the wafer resistivity can be directly obtained. Since the eddy current density is the highest on the surface, the quality of the surface state directly affects the test accuracy. For conductive silicon carbide wafers, the general surface state measurement parameters include physical parameters such as surface contamination, surface roughness, flatness, warpage, and surface defects. These parameters will affect the change of surface eddy currents. Generally speaking, these defects will cause the eddy currents to become smaller, which will make the resistivity data obtained by the test larger. In order to solve these problems, wafers are usually processed in industry, and the processing flow is: crystal rod cutting → grinding → mechanical polishing → chemical mechanical polishing. After continuous processing, the wafer becomes more flat and the surface contamination is cleaned, making it easier to test the resistivity. Usually, the resistivity test is done after the grinding process.

[0004] If the resistivity data can be obtained after the wafer is cut, the unqualified wafers can be screened out, which will save a considerable amount of grinding and cleaning capacity. In addition, resistivity testing at the beginning of wafer processing (after cutting) will reduce the introduction of unnecessary scratches on the finished wafer and improve the yield. In summary, testing the resistivity immediately after the wafer is cut can save costs and reduce unnecessary wafer damage, so we propose a resistivity test solution here.

[0005] At present, the resistivity test of conductive silicon carbide wafers is carried out after the grinding process, not after the wafers are cut. After cutting, subsequent grinding and cleaning are required before the resistivity test can be carried out. In this way, some wafers with unqualified resistivity will also be transferred to the grinding and post-grinding cleaning processes, squeezing the grinding and cleaning capacity. And after cutting, these unqualified wafers will also be chamfered, which is unnecessary waste and increases production costs. Moreover, during the resistivity test, the wafer must directly contact the metal base of the test instrument. During the contact process, it is very easy to introduce additional scratches, which is not conducive to further transmission and processing. Therefore, it is very necessary to perform resistivity testing in the early stages of silicon carbide wafer processing.

[0006] Chinese patent CN111320982A - A micro-etching roughening agent for silicon wafer surface and its treatment method discloses the use of a micro-etching roughening agent to perform micro-etching roughening treatment on the surface of a silicon wafer after chemical polishing, so that the surface of the silicon wafer forms a uniform inverse cosine structure, thereby improving the metal wiring yield in the subsequent process. Mixed acid and other solutions are used, but they are ultimately for later wiring. They do not pay attention to the problem of the wafer's early resistivity, and they process ordinary silicon wafers. If silicon carbide wafers are processed, the surface morphology will be affected, affecting the measurement results.

[0007] The main reason why wafer resistivity testing is not generally performed after cutting in the prior art is that the surface condition of the wafer after cutting is poor, and the resistivity result obtained by direct testing is larger than the true value. In this way, some qualified wafers are easily judged as unqualified, which affects the yield. However, if processing is performed, it is easy to affect the accuracy of the measurement results. Summary of the invention

[0008] In order to solve the above problems, a method for testing the resistivity of a conductive silicon carbide wafer after cutting is provided. By using a limited type of solution for cleaning, the roughness of the wafer can be reduced, and the resistivity testing process can be advanced to before grinding, saving processing costs. At the same time, by matching the specific point distribution, the resistivity data of the entire silicon carbide wafer can be obtained, and the resistivity distribution and uniformity of each area of ​​the wafer can be comprehensively evaluated, providing a more accurate basis for judging the wafer quality.

[0009] According to one aspect of the present application, a method for testing the resistivity of a conductive silicon carbide wafer after cutting is provided, comprising the following steps:

[0010] a. Segmented cleaning: Place the cut silicon carbide wafers in a basket and soak them in an acid-base tank containing an organic solvent, acid or alkali solution, and water in turn. After cleaning, ultrasonicate them in an ultrasonic machine filled with an organic solvent and dry them.

[0011] b. Use the FRT surface tester to test the thickness of multiple points on the wafer surface, and finally obtain the average value of the thickness data;

[0012] c. Use a non-contact resistivity tester, input the average thickness of the wafer, set the test points according to the point distribution, and test each point twice with the detection head. Finally, draw a resistivity distribution map of the entire wafer surface and count the maximum, minimum and average values.

[0013] Optionally, in step a, four acid-base tanks are used, which are respectively filled with anhydrous ethanol, hydrofluoric acid, hydrochloric acid and ultrapure water. The flower basket loaded with wafers passes through the four acid-base tanks in sequence, and is finally ultrasonicated in an ultrasonic machine filled with anhydrous ethanol.

[0014] Optionally, in step a, hydrofluoric acid with a mass percentage concentration of 2-5% and hydrochloric acid with a mass percentage concentration of 85-88% are used, and the conductivity of ultrapure water is below 2 μS / cm.

[0015] Optionally, in step a, three acid-base tanks are used, which are respectively filled with anhydrous ethanol, potassium hydroxide or sodium hydroxide solution and ultrapure water. The flower basket loaded with wafers passes through the three acid-base tanks in sequence, and is finally ultrasonicated in an ultrasonic machine filled with anhydrous ethanol.

[0016] Optionally, the potassium hydroxide or sodium hydroxide solution with a mass percentage concentration of 45-50% is used in step a, and the conductivity of ultrapure water is below 2 μS / cm.

[0017] Optionally, the temperature of the solution in each acid-base tank is 70-80° C., and the flower basket stays in each acid-base tank for at least 5 minutes.

[0018] Optionally, the ultrasonic power is 140-160W, the ultrasonic frequency is 10-50kHz, and the ultrasonic time is 3-5min; the drying method is to wipe the surface of the wafer clean with a clean non-woven cloth or blow it dry with a nitrogen gun, and put it in a clean room for testing.

[0019] Preferably, the ultrasonic power is 150 W, the ultrasonic frequency is 30 kHz, and the ultrasonic time is 4 min.

[0020] Optionally, in step c, the surface of the sample workbench for resistivity test is wiped clean with alcohol, and the wafer must be placed with the silicon side facing upward. After placement, enter the average thickness of the wafer in μm, accurate to one decimal place.

[0021] Optionally, in step c, a 73-point test method is used to measure the resistivity, with the center of the wafer as the center, and 8 concentric circles with radii of 8 mm, 16 mm, 24 mm, 32 mm, 40 mm, 48 mm, 56 mm and 64 mm are formed outward, and at the same time, radial lines with an interval of 20° are formed outward from the center of the circle and intersect with each concentric circle.

[0022] Optionally, with the center of the circle as the first point, an intersection point is selected as the measurement point at intervals of one radial line on the smallest concentric circle, 9 intersection points are selected as the measurement points on each concentric circle, and the measurement points of adjacent concentric circles are not on the same radial line.

[0023] The beneficial effects of this application include but are not limited to:

[0024] 1. According to the method for testing the resistivity of the conductive silicon carbide wafer after cutting of the present application, by limiting the cleaning solution and sequence, the surface contamination is removed, the surface roughness is reduced, the surface state is changed, the influence of the surface on the size of the eddy current is reduced, and the test accuracy is improved; at the same time, by matching specific distribution points, accurate resistivity data can be obtained, and the operation process is simple, the surface state of the wafer can be improved, and it is suitable for the resistivity test of conductive silicon carbide wafers of different sizes and thicknesses.

[0025] 2. According to the method for testing the resistivity of the conductive silicon carbide wafer after cutting of the present application, by limiting the cleaning sequence and concentration of the solution mainly composed of acid solution, anhydrous ethanol is first used as the initial cleaning solution to remove organic residues and dust on the surface of the wafer and purify the surface, and then a limited concentration of hydrofluoric acid is used to effectively remove the oxide and oxide layer on the surface of the wafer, reduce surface contamination without seriously corroding the surface of the wafer, and avoid damage. The use of a limited concentration of hydrochloric acid can remove metal ions and other impurities on the surface of the wafer, and further improve the purity of the wafer. The use of ultrapure water with a limited conductivity can reduce the impact of moisture on the wafer, avoid moisture residue and ion contamination, and improve the accuracy of the test; finally, after multiple stages of chemical cleaning, the wafer is cleaned with ultrasound, which can further remove the difficult-to-remove tiny contamination on the surface, and the cleaning effect is more thorough. Anhydrous ethanol is used as an ultrasonic medium and will not cause damage to the wafer;

[0026] If an alkaline solution of a limited concentration is used for cleaning, the metal ions on the surface can be effectively chelated without seriously corroding the wafer surface and causing damage.

[0027] 3. According to the method for testing the resistivity of the conductive silicon carbide wafer after cutting of the present application, by limiting the specific temperature and time, matching the cleaning solution with the limited concentration, the chemical reaction rate can be accelerated, the reaction of the pollutants and the cleaning solution can be accelerated, the cleaning efficiency can be improved, and the cleaning effect can be maximized without damage.

[0028] 4. According to the method for testing the resistivity of the conductive silicon carbide wafer after cutting of the present application, by innovatively arranging the 73-point test method, on the one hand, it can better reflect the resistivity in the polar axis and polar angle directions, accurately characterize the resistivity of the entire surface of the wafer, comprehensively test the resistivity of each area of ​​the wafer, and evaluate the uniformity and distribution of the wafer resistivity based on the test results, providing an accurate basis for judging the quality of the wafer; on the other hand, it can eliminate the influence of local surface conditions on the test results, obtain a more accurate average resistivity value of the wafer, provide richer and more detailed resistivity information, reveal the change trend and local differences of the wafer surface resistivity, and finally provide a more accurate basis for judging the quality of the wafer. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0030] Figure 1 This is a schematic diagram comparing the roughness of a wafer before and after the cleaning process involved in this application.

[0031] Figure 2 This is a schematic diagram of the distribution of 73 points involved in the embodiment of the present application.

[0032] Figure 3 This is an atomic force microscope comparison diagram of the roughness of the wafer before cleaning and after being processed in Example 1 after cutting involved in the present application.

[0033] Figure 4 This is a resistivity detection diagram of the wafer before cleaning and after being processed in Example 1 after being cut into pieces involved in the present application.

[0034] Figure 5 This is the resistivity test diagram after the comparative example 1 is processed.

[0035] Figure 6 This is the resistivity test diagram after the comparative example 2 is processed.

[0036] Figure 7 This is the point distribution diagram of Comparative Example 3 and the resistivity test diagram after treatment. DETAILED DESCRIPTION

[0037] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0038] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in this patent are for demonstration purposes only.

[0039] Example 1

[0040] The method for testing the resistivity of a conductive silicon carbide wafer after cutting comprises the following steps:

[0041] a. Segmented cleaning: Place the cut silicon carbide wafers in a basket and soak them in acid-base tanks containing organic solvents, acid solution, and water in turn. After cleaning, ultrasonicate them in an ultrasonic machine filled with organic solvents and dry them.

[0042] b. Use the FRT surface tester to test the thickness of multiple points on the wafer surface, and finally obtain the average value of the thickness data;

[0043] c. Use a non-contact resistivity tester, input the average thickness of the wafer, set the test points according to the point distribution, and test each point twice with the detection head. Finally, draw a resistivity distribution map of the entire wafer surface and count the maximum, minimum and average values.

[0044] In step a, four acid-base tanks are used, which are respectively filled with anhydrous ethanol, hydrofluoric acid, hydrochloric acid and ultrapure water. The basket loaded with wafers passes through the four acid-base tanks in sequence, and finally is ultrasonicated in an ultrasonic machine filled with anhydrous ethanol. Hydrofluoric acid with a mass percentage concentration of 2% and hydrochloric acid with a mass percentage concentration of 85% are used in step a, and the conductivity of ultrapure water is below 2μS / cm.

[0045] The temperature of the solution in each acid-base tank is 75°C, and the flower basket stays in each acid-base tank for 5 minutes. The ultrasonic power is 140W, and the ultrasonic time is 5 minutes; the drying method is to wipe the surface of the wafer with a clean non-woven cloth and put it in the clean room for testing. In step c, wipe the surface of the sample operating table for resistivity test with alcohol. When placing the wafer, the silicon side must face up. After placing it, enter the average thickness of the wafer in μm, accurate to one decimal place.

[0046] Figure 1 The above figure is a schematic diagram of the comparison of wafer roughness before and after treatment. The upper figure is before treatment, and the lower figure is after treatment in Example 1. Figure 3 As shown in FIG. 1 , this is the result obtained by using an atomic force microscope test. The roughness before cleaning is 200 nm, and after cleaning using this embodiment, it is 60 nm.

[0047] In step c, the resistivity is measured using a 73-point test method. With the center of the wafer as the center, eight concentric circles with radii of 8 mm, 16 mm, 24 mm, 32 mm, 40 mm, 48 mm, 56 mm and 64 mm are formed outward. At the same time, radial lines with intervals of 20° are formed outward from the center of the circle to intersect with each concentric circle. With the center of the circle as the first point, an intersection point is selected as the measurement point every other radial line on the smallest concentric circle. Nine intersection points are selected as measurement points on each concentric circle. The measurement points of adjacent concentric circles are not on the same radial line, for a total of 73 points. Specifically, Figure 2 The midpoint distribution is shown.

[0048] like Figure 4 As shown, the maximum, minimum and average values ​​are calculated. Figure 4 By comparing the resistivity data before and after the cleaning process, it can be seen that more accurate and comprehensive resistivity data are obtained after the cleaning process of Example 1.

[0049] Example 2

[0050] The method for testing the resistivity of a conductive silicon carbide wafer after cutting comprises the following steps:

[0051] a. Segmented cleaning: Place the cut silicon carbide wafers in a basket and soak them in acid-base tanks containing organic solvents, acid solution, and water in turn. After cleaning, perform ultrasonic cleaning in an organic solvent and dry.

[0052] b. Use the FRT surface tester to test the thickness of multiple points on the wafer surface, and finally obtain the average value of the thickness data;

[0053] c. Use a non-contact resistivity tester, input the average thickness of the wafer, set the test points according to the point distribution, and test each point twice with the detection head. Finally, draw a resistivity distribution map of the entire wafer surface and count the maximum, minimum and average values.

[0054] In step a, four acid-base tanks are used, which are respectively filled with anhydrous ethanol, hydrofluoric acid, hydrochloric acid and ultrapure water. The basket loaded with wafers passes through the four acid-base tanks in sequence, and finally is ultrasonicated in an ultrasonic machine filled with anhydrous ethanol. Hydrofluoric acid with a mass percentage concentration of 4% and hydrochloric acid with a mass percentage concentration of 87% are used in step a, and the conductivity of ultrapure water is below 2μS / cm.

[0055] The temperature of the solution in each acid-base tank is 70℃, and the flower basket stays in each acid-base tank for 5 minutes. The ultrasonic power is 150W, and the ultrasonic time is 4 minutes; the drying method is to blow dry with a nitrogen gun and put it in the clean room for testing. In step c, wipe the surface of the sample workbench for resistivity test with alcohol. When placing the wafer, the silicon side must face up. After placing, enter the average thickness of the wafer in μm, accurate to one decimal place.

[0056] In step c, the resistivity is measured by the 73-point test method. With the center of the wafer as the center, eight concentric circles with radii of 8 mm, 16 mm, 24 mm, 32 mm, 40 mm, 48 mm, 56 mm and 64 mm are formed outward. At the same time, radial lines with intervals of 20° are formed outward from the center of the circle to intersect with each concentric circle. With the center of the circle as the first point, one intersection point is selected as the measurement site on the smallest concentric circle at intervals of one radial line. Nine intersection points are selected as the measurement sites on each concentric circle. The measurement sites of adjacent concentric circles are not on the same radial line, for a total of 73 points.

[0057] Example 3

[0058] The method for testing the resistivity of a conductive silicon carbide wafer comprises the following steps:

[0059] a. Segmented cleaning: Place the cut silicon carbide wafers in a basket and soak them in acid-base tanks containing organic solvents, alkali solutions, and water in turn. After cleaning, perform ultrasonic cleaning in an organic solvent and dry.

[0060] b. Use the FRT surface tester to test the thickness of multiple points on the wafer surface, and finally obtain the average value of the thickness data;

[0061] c. Use a non-contact resistivity tester, input the average thickness of the wafer, set the test points according to the point distribution, and test each point twice with the detection head. Finally, draw a resistivity distribution map of the entire wafer surface and count the maximum, minimum and average values.

[0062] Among them, three acid-base tanks are used in step a, and anhydrous ethanol, sodium hydroxide solution and ultrapure water are respectively loaded. The flower basket loaded with wafers passes through the three acid-base tanks in turn, and finally ultrasonicated in an ultrasonic machine filled with anhydrous ethanol. The sodium hydroxide solution used in step a is 45% by mass percentage, and the conductivity of ultrapure water is below 2μS / cm. The temperature of the solution in each acid-base tank is 75°C, and the flower basket stays in each acid-base tank for 5 minutes. The ultrasonic power is 160W, and the ultrasonic time is 3min; the drying method is to wipe the surface of the wafer with a clean non-woven fabric and put it in the clean room for testing. In step c, the surface of the sample operating table for the resistivity test is wiped clean with alcohol. When placing the wafer, the silicon side must be facing up. After placement, enter the average thickness of the wafer in μm, accurate to one decimal place.

[0063] In step c, the resistivity is measured using a 73-point test method. With the center of the wafer as the center, eight concentric circles with radii of 8 mm, 16 mm, 24 mm, 32 mm, 40 mm, 48 mm, 56 mm and 64 mm are formed outward. At the same time, radial lines with an interval of 20° are formed outward from the center of the circle and intersect with each concentric circle.

[0064] Taking the center of the circle as the first point, an intersection point is selected as the measurement point every other radial line on the smallest concentric circle. Nine intersection points are selected as measurement points on each concentric circle. The measurement points of adjacent concentric circles are not on the same radial line, totaling 73 points.

[0065] Comparative Example 1

[0066] The difference between Comparative Example 1 and Example 1 is that only 5% hydrofluoric acid is used in Comparative Example 1.

[0067] Figure 5 The resistivity data in the figure are after being treated with 5% hydrofluoric acid. The selected wafer is adjacent to the wafer in Example 1. It can be seen from the figure that the resistivity after treatment is more uneven and the effect is poor.

[0068] Comparative Example 2

[0069] The difference between Comparative Example 2 and Example 1 is that: in step a of Comparative Example 2, hydrofluoric acid with a mass percentage concentration of 10% and hydrochloric acid with a mass percentage concentration of 50% are used. The selected wafer is adjacent to the wafer in Example 1, such as Figure 6 The resistivity after treatment is still quite different from that in Example 1.

[0070] Comparative Example 3

[0071] The difference between Comparative Example 3 and Example 1 is that the measurement points in Comparative Example 3 are measured in other ways, such as Figure 7 As shown in the left figure, there are also 73 points in the test. The difference from Example 1 is that radial lines are formed outward from the center of the circle at intervals of 22.5°. Each concentric circle has 8 points, and the outermost circle has 16 points. The selected wafer is adjacent to the wafer in Example 1, such as Figure 7 The resistivity edge after treatment is larger as shown in the right figure.

[0072] Experimental example

[0073] The untreated wafers, Example 1, and Comparative Examples 1-3 were tested according to conventional testing methods to obtain average resistivity and variance data as shown in Table 1.

[0074] Table 1 Average resistivity and variance data

[0075]

[0076] As can be seen from the above table, the average resistivity of Example 1 is the smallest, and the variance is the smallest, which indicates that the method of Example 1 can obtain more accurate and more evenly distributed resistivity values ​​with high precision.

[0077] It can be seen from the accompanying drawings that the cleaning method and measurement points specified in this application ultimately have a good effect on the wafer surface treatment, which is conducive to accurate subsequent measurements. The specific point distribution can obtain the resistivity data of the entire silicon carbide wafer, and can comprehensively evaluate the resistivity distribution and uniformity of each area of ​​the wafer, providing a more accurate basis for judging the wafer quality.

[0078] Comparative Example 1 uses a single acid for treatment, which has a general cleaning effect on the wafer and is likely to affect the accuracy of subsequent measurements; the acid concentration used in Comparative Example 2 exceeds the range specified in this application, which is likely to cause excessive etching on the wafer surface and affect the measurement results; the point distribution in Comparative Example 3 ultimately cannot fully reflect the resistivity of the wafer, and it is difficult to provide an accurate basis for the final judgment.

[0079] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for testing the resistivity of a conductive silicon carbide wafer after cutting, characterized in that: The following steps are involved: a. Segmented cleaning: Place the cut silicon carbide wafers in a basket and soak them in an acid-base tank containing an organic solvent, acid or alkali solution, and water in turn. After cleaning, ultrasonicate them in an ultrasonic machine filled with an organic solvent and dry them. b. Use the FRT surface tester to test the thickness of multiple points on the wafer surface and obtain the average value of the thickness data; c. Use a non-contact resistivity tester, input the average thickness of the wafer, set the test points using a 73-point test point distribution, test each point twice with the probe head, draw a resistivity distribution map of the entire wafer surface, and count the maximum, minimum, and average values; Wherein, in step c, a 73-point test is used to measure the resistivity, with the center of the wafer as the center, and 8 concentric circles with radii of 8 mm, 16 mm, 24 mm, 32 mm, 40 mm, 48 mm, 56 mm and 64 mm are formed outward, and at the same time, radial lines with intervals of 20° are formed outward from the center of the circle to intersect with each concentric circle; with the center of the circle as the first point, an intersection point is selected as a measurement site on the smallest concentric circle at intervals of one radial line, and 9 intersection points are selected as measurement sites on each concentric circle, and the measurement sites of adjacent concentric circles are not on the same radial line; In step a, four acid-base tanks are used, which are respectively filled with anhydrous ethanol, hydrofluoric acid, hydrochloric acid and ultrapure water. The flower basket loaded with wafers passes through the four acid-base tanks in sequence, and is finally ultrasonicated in an ultrasonic machine filled with anhydrous ethanol. The hydrofluoric acid with a mass percentage concentration of 2-5% and the hydrochloric acid with a mass percentage concentration of 85-88% are used in step a, and the conductivity of the ultrapure water is below 2μS / cm.

2. The method for testing the resistivity of a conductive silicon carbide wafer after cutting according to claim 1, characterized in that: The temperature of the solution in each acid-base tank is 70-80℃, and the flower basket stays in each acid-base tank for at least 5 minutes.

3. The method for testing the resistivity of a conductive silicon carbide wafer after cutting according to claim 2, characterized in that: The ultrasonic power is 140-160W, the ultrasonic frequency is 10-50kHz, and the ultrasonic time is 3-5min; The drying method is to wipe the wafer surface with a clean non-woven cloth or blow it dry with a nitrogen gun, and then place it in a clean room for testing.

4. The method for testing the resistivity of a conductive silicon carbide wafer after cutting according to claim 1, characterized in that: In step c, wipe the surface of the sample workbench for testing resistivity with alcohol. The wafer must be placed with the silicon side facing up. After placement, enter the average thickness of the wafer in μm, accurate to one decimal place.

Citation Information

Patent Citations

  • Wafer silicon wafer surface micro-etching roughening treatment agent and treatment method thereof

    CN111320982A

  • Chemical passivation method for measuring minority carrier lifetime of crystalline silicon

    CN101162694A

  • Method for determining conduction type of silicon wafer

    CN113655094A